(untitled) (Research, Society and Development, 2025)
Inspiratory muscle training (IMT) is a technique aimed at improving the weaning process from ventilatory support. This study evaluates the impact of IMT on inspiratory muscle strength, the duration of mechanical ventilation (MV), and the need for tracheostomy in critically ill patients. Methodology: This randomized, controlled, double-blind trial was conducted at the adult ICU of Maria Aparecida Pedrossian University Hospital (HUMAP). Both the evaluator and statistician were blinded to group assignments. IMT was administered twice daily, five days a week. The intervention group underwent IMT with a resistance load of 45% to 55% of maximal inspiratory pressure (Pimax), while the placebo group received IMT without any load. Results: The study included 29 patients: 14 in the intervention group and 15 in the placebo group. The intervention group showed significant improvements in inspiratory muscle strength (p=0.007), a reduction of 2.7 days in MV duration (p=0.012), and a lower percentage of tracheostomy (p=0.016) compared to the placebo group. Discussion: The findings suggest that IMT offers benefits in the ventilatory weaning process. However, existing literature presents mixed results on its impact on MV duration, and there is limited evidence regarding its effect on tracheostomy rates. Conclusion: This study concludes that IMT can enhance inspiratory muscle strength, shorten the duration of mechanical ventilation, and reduce the need for tracheostomy in ICU patients at HUMAP.